Unpacking the revised Bloom's taxonomy: developing case-based learning activities. Issue 3 (13th March 2017) - Nkhoma, Mathews Zanda; Lam, Tri Khai; Sriratanaviriyakul, Narumon; Richardson, Joan; Kam, Booi; Lau, Kwok Hung
Abstract : Purpose: The purpose of this paper is to propose the use of case studies in teaching an undergraduate course of Internet for Business in class, based on the revised Bloom's taxonomy. The study provides the empirical evidence about the effect of case-based teaching method integrated the revised Bloom's taxonomy on students' incremental learning, measured by the four constructs: knowledge application, higher-order thinking, practice evaluation knowledge and knowledge improvement. Design/methodology/approach: In this study, learning activities associated with the revised taxonomy-based learning strategy were proposed to support the development of higher-level cognitive skills. Revised application scale, higher-order thinking scale, practice evaluation knowledge scale and knowledge improvement scale were used to measure students' perception of skills corresponding to their level of application, analysis, evaluation and creation, respectively. After completing each task pertinent to case studies, students were encouraged to complete the survey questionnaire. Structural equation modelling (SEM) was employed to examine the relationships between constructs. Students participate in a course where case studies are employed as the main learning activities to promote higher-order thinking. Upon completing the course, they fill in a survey to evaluate the four constructs of incremental learning: level of knowledge application, higher-order thinking, practice evaluation knowledge and knowledge improvement. The relationships between the four constructs are then examined using SEM. Findings: Analysis reveals that with the use of case-based learning activities, knowledge application creates a positive impact on higher-order thinking. Higher-order thinking has positive influence on practice evaluation knowledge. Eventually, practice evaluation knowledge produces a positive effect on knowledge improvement. The results show the desired effects of incremental learning. Research limitations/implications: The case studies designed for teaching the Internet for Business course might not be suitable in terms of content for other courses, which limit the implication of the findings. Practical implications: The key implication is that cognitive process is enhanced by using case studies where learning activities are designed, based on the revised Bloom's taxonomy. Originality/value: The paper offers a comprehensive perspective on incremental learning where students' knowledge of Internet for Business moves developmentally towards the higher-order cognitive process dimension of the revised Bloom's taxonomy.